Pengaruh Brand Image Terhadap Keputusan Pembelian Sepatu Converse Dimediasi Brand Trust (Studi Pada Official Store Di Tunjungan Plaza) - Aziz, Moh. Waladil; Andriani, Nurita (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
When buying Converse shoes at the Official Store Tunjungan Plaza Surabaya, the aim of this research is to find out and test whether brand image has a good and significant influence on purchasing decisions, with brand trust as a mediating factor. Using a quantitative approach with a focus on one Converse store in Tunjungan Plaza Surabaya and survey design using linear regression data analysis is an efficient way to measure and track the performance of this research. Purposive sampling was used to select 100 respondents as the sample size. Based on research findings, trust in the Converse shoe brand is positively and significantly influenced by brand image. In addition, brand perception significantly and positively influences the decision to purchase Converse shoes, both through direct and indirect relationships. The direct influence of Brand Image on Purchasing Decisions is stronger than the indirect influence through Brand Trust. Brand trust has a positive and significant effect on the decision to purchase Converse shoes. This shows that a positive brand image helps build consumer trust in the brand and helps strengthen consumer decisions in purchasing a product